2022
DOI: 10.1111/obr.13482
|View full text |Cite
|
Sign up to set email alerts
|

Co‐creation of healthier food retail environments: A systematic review to explore the type of stakeholders and their motivations and stage of engagement

Abstract: Objective: To synthesize peer-reviewed literature that utilize co-creation principles in healthy food retail initiatives.Methods: Systematic review of six databases from inception to September 2021.Screening and quality assessment were carried out by two authors independently.Studies were included if they were conducted in food retail stores, used a collaborative model, and aimed to improve the healthiness of the food retail environment.Studies excluded were implemented in restaurants, fast food chains, or sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 94 publications
2
4
0
Order By: Relevance
“…Cocreation is frequently implemented in deprived communities, and it is an appropriate instrument for meeting public health objectives [ 28 , 29 ]. In line with the critiques given by Vargas et al, we agree that projects tend to focus more on the implementation of the actions, rather than the processes used to elicit community participation in the cocreation process [ 63 ]. Harnessing the full power of co-created public health initiatives to tackle health inequalities will require community members to be actively and equitably involved in all phases of the action.…”
Section: Discussionsupporting
confidence: 73%
“…Cocreation is frequently implemented in deprived communities, and it is an appropriate instrument for meeting public health objectives [ 28 , 29 ]. In line with the critiques given by Vargas et al, we agree that projects tend to focus more on the implementation of the actions, rather than the processes used to elicit community participation in the cocreation process [ 63 ]. Harnessing the full power of co-created public health initiatives to tackle health inequalities will require community members to be actively and equitably involved in all phases of the action.…”
Section: Discussionsupporting
confidence: 73%
“…The systematic review identified 23 articles that utilized various aspects of cocreation to improve the healthiness of food retail environments. 19 Cocreation of healthy food retail was most commonly used when developing initiatives with specific population groups, such as lower socioeconomic and indigenous communities where the needs and perspectives of these groups that are often marginalized in decision making may be overlooked. 32 , 33 , 34 , 35 , 36 Key elements of cocreation were the type of stakeholders involved, their level of engagement, and their motivations.…”
Section: Resultsmentioning
confidence: 99%
“… 32 , 33 , 34 , 35 , 36 Key elements of cocreation were the type of stakeholders involved, their level of engagement, and their motivations. 19 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since improving food retail environments in collaboration with retailers is a relatively new approach, it is common to see academic researchers [ 69 ] or organizations such as CHS leading the implementation and providing the funding. It could be theorized that figures/organizations holding the funds to conduct health-enabling strategies in food retail outlets will assume the leadership role, causing a power imbalance in this multi-stakeholder relationship.…”
Section: Discussionmentioning
confidence: 99%